The Russian Pronoun Nekotoryj in light of Typological Expectations - Olga E. Pekelis (Studi Slavistici)
This paper investigates the synchronic traits and the microdiachronic evolution of the Russian pronoun nekotoryj. Synchronically, I argue that nekotoryj has four different meanings, with the meaning of an indefinite pronoun being the most frequent and the least distributionally restricted. Diachronically, nekotoryj is shown to have had an article-like function in the Russian language of the 19th century and earlier, which it shared with the numeral odin ‘one,’ while in modern Russian this function is undertaken by odin alone. Within a typological stance on the facts observed, I suggest that nekotoryj displays both expected and unexpected traits. The former includes the outcome of its competition with odin. The latter concerns the distribution of nekotoryj across the contexts that make up the semantic map of indefinite pronouns. Nekotoryj appears to be an instance of an indefinite pronoun that contradicts some predictions put forward by the semantic map.